Dukungan Indonesia sebagai Regional Power di Asia Tenggara terhadap Keanggotaan Timor Leste di ASEAN - Salsa Faiz Luthfiyyah; Nur Luthfi Hidayatullah (Department of International Relations, Brawijaya University, 2026)
This study aims to describe Indonesia’s role as a regional power in Southeast Asia in expanding the membership of the ASEAN regional organization, using East Timor’s membership as a case study. The author argues that, as a regional power in Southeast Asia and “first among equals” in ASEAN, Indonesia’s support is crucial for the admission of new members to ASEAN. This study employs a qualitative descriptive method, utilizing secondary data sources. The data collection techniques employed by the author include documentation and literature review. The results of this study indicate that, as a regional power, Indonesia assisted Timor-Leste in joining ASEAN as a member state through four means: claims, ideas, resources, and foreign policy. First, Indonesia used claims to promote Timor-Leste’s membership in ASEAN and to convince countries that had previously opposed it. Second, Indonesia employed ideas to develop a roadmap for Timor-Leste’s accession to ASEAN and initiated a summit to discuss Timor-Leste’s membership. Third, Indonesia utilized resources to establish economic cooperation with Timor-Leste and provided opportunities for Timor-Leste civil servants to undertake internships at government agencies of the Republic of Indonesia. Fourth, Indonesia employed foreign policy by inviting Timor-Leste to the ASEAN Summit and the East Asia Summit.